The cytokine il‐1β and piperine complex surveyed by experimental and computational molecular biophysics - Zazeri, Gabriel [UNESP]; Povinelli, Ana Paula Ribeiro [UNESP]; Lima, Marcelo de Freitas [UNESP]; Cornélio, Marinônio Lopes [UNESP] (MDPI, 2020)
The bioactive piperine, a compound found in some pepper species, has been widely studied because of its therapeutic properties that include the inhibition of an important inflammation pathway triggered by interleukin‐1 beta (IL‐1β). However, investigation into the molecular interactions between IL‐1β and piperine is not reported in the literature. Here, we present for the first time the characterisation of the complex formed by IL‐1β and piperine through experimental and computational molecular biophysical analyses. Fluorescence spectroscopy unveiled the presence of one binding site for piperine with an affinity constant of 14.3 × 104 M−1 at 298 K. The thermodynamic analysis indicated that the interaction with IL‐1β was spontaneous (∆G = −25 kJ/mol) and, when split into enthalpic and entropic contributions, the latter was more significant. Circular dichroism spectroscopy showed that piperine did not affect IL‐1β secondary structure (~2%) and therefore its stability. The set of experimental data parameterized the computational biophysical approach. Through molecular docking, the binding site micro‐environment was revealed to be composed mostly by non‐polar amino acids. Furthermore, molecular dynamics, along with umbrella sampling, are in agreement with the thermodynamic parameters obtained by fluorescence assays and showed that large protein movements are not present in IL‐1β, corroborating the circular dichroism data.
Keywords: Cytokine; Fluorescence spectroscopy; IL‐1β; Molecular docking; Piperine; Umbrella sampling